2002
DOI: 10.1067/mtc.2002.118686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target stenosis and location on radial artery graft patency

Abstract: Radial artery patency is sensitive to both target location and proximal target stenosis. Selective use of the radial artery to targets of the left anterior descending and circumflex distributions remains encouraging. Radial artery grafts to targets of the right coronary artery or those with moderate stenosis appear to be at particularly high risk of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
102
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 24 publications
5
102
2
3
Order By: Relevance
“…Multiple studies have replicated these findings, which indicates that early angiographic patency with radial artery grafts in the modern era consistently exceeds 90% and is similar to results achieved with the IMA. [7][8][9][10][11][12][13] In addition to these reports, the increasing acceptance of the radial artery has been based on 2 studies with angiographic results, both with 5 years of follow-up. In one, angiography in 50 patients with 64 radial grafts revealed a patency rate of 83%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have replicated these findings, which indicates that early angiographic patency with radial artery grafts in the modern era consistently exceeds 90% and is similar to results achieved with the IMA. [7][8][9][10][11][12][13] In addition to these reports, the increasing acceptance of the radial artery has been based on 2 studies with angiographic results, both with 5 years of follow-up. In one, angiography in 50 patients with 64 radial grafts revealed a patency rate of 83%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent larger study of 109 patients who underwent cardiac catheterization for symptoms of ischemia showed an overall patency rate of the radial artery graft of only 75.1% at a mean follow-up of 2.3 years. 13 Improvements in harvesting techniques and postoperative administration of calcium channel blockers were expected to lead to improved results with the radial artery, yet we are concerned that these technical advances and pharmacological therapies have merely delayed the ultimate poor outcome with these grafts. The exact mechanism for the observed high rate of radial artery graft failure is not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations